Karya Nyata Mahasiswa Dengan Mewujudkan Lingkungan Bersih Dan Tertata Melalui Edukasi, Gotong Royong, Dan Pemasangan Plang Jalan - Oktavia, Ferda; Kusumawarty, Pratiwi; Toresman, Amza; Aulia, Rifah; Herlyaminda, Evi; Suwarni, Suwarni; Soleh, Ahmad (Utami Publisher, 2025)
This real work aims to create a clean and orderly environment in the community through education, mutual cooperation, and the installation of road signs. This activity was carried out by students as part of community service. The methods used include counseling on the importance of environmental cleanliness, mutual cooperation to clean the environment, and the installation of road signs to increase public awareness. The results of the activity show an increase in public awareness about penting.